Effectiveness of a Diet Exercise Educational Program on Patient's Knowledge to Prevent Coronary Artery Disease Progression After Percutaneous Coronary Intervention - Halla F. Abdul-Ameer, Khalida M. Khuder, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: While COVID-19 continues to claim the lives of more than 5 million people each year, cardiovascular disease (CVD) caused the death of over 186 million people each year. Coronary heart disease (CHD), CVD, rheumatic heart disease, and other heart and blood vessel problems are all classified as CVDs. In 2019, CVDs were responsible for 38 percent of the 17million premature deaths produced by non-communicable diseases (before the age of 70). Lifestyle threats such as cigarette smoking, poor diet and obesity, lack of physical activity, and alcoholism can all be avoided (WHO, 2021). Aims: To assess the patient's levels of knowledge about the effects of exercises and diet to prevent coronary artery disease progression after percutaneous coronary intervention, To find out the relationship between patients’ knowledge with their selected demographic variables (age, gender, education level, occupational status, and marital status), and to Find out the association between patients’ knowledge concerning diet and exercise after the application of the educational program in the post-test period. Methodology: Pre-experimental design (one group pretest-posttest) A non-probability (purposive) sample of 35 patients. The study started from November 2021 to May 2022. Result: The majority of CAD patients are males with age 48 and above, married, secondary school graduates, and housewives. More than half of the study sample had risk factors for coronary artery disease, except for the patient's own smoking. Patients with coronary artery disease had a low degree of knowledge about healthy lifestyles before beginning the educational program. A significant improvement in patients’ knowledge regarding healthy lifestyles after giving them the educational program, and there is no relationship between patients' knowledge and socio-demographic characteristics with the exception of gender. Conclusion: A significant improvement in patient’s knowledge regarding healthy lifestyles after giving them the educational program